Implementation of Data Mining on Sales Data of Bambu Ungu Cafe to Find out Consumer Purchasing Patterns Using the Apriori Algorithm - Fadli, Rahmad; Ruziq, Fahmi; Imam, Chairul (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
In today's digital age, restaurants or cafes face increasing competition and complex challenges. To stay relevant and succeed in this business, the use of data mining is crucial, as it becomes a valuable tool in optimizing sales, increasing customer satisfaction, and achieving long-term success in the restaurant and café industry. Data mining helps in effective marketing strategies. By analyzing customer data, purchase information, and preferences restaurants and cafes can identify different customer segments and create customized marketing. With so much sales transaction data, it will certainly be difficult if the data is analyzed manually, therefore information will be obtained if there is processing with the help of a system to get sales patterns. The results of this processing will produce transaction information to support product transaction decisions. To solve this problem, the researcher designed a calculation information system. In this case the author uses the waterfall method in the research process. For system design the author uses the PHP programming language with a database format using MySQL. Finally, with this information system, the calculation process can be done automatically without the need to calculate manually is appropriate, provided that all data inputted is valid.